2022
DOI: 10.1001/jamanetworkopen.2022.33014
|View full text |Cite
|
Sign up to set email alerts
|

Association of SARS-CoV-2 Infection With New-Onset Type 1 Diabetes Among Pediatric Patients From 2020 to 2021

Abstract: This cohort study assesses the association of COVID-19 with new-onset type 1 diabetes among pediatric patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
82
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(85 citation statements)
references
References 5 publications
2
82
1
Order By: Relevance
“… [34] Finally, in another US study, new-onset diabetes was increased in children aged 10-18 years at 3 months (HR: 2.40 (1.62-3.56)) and 6 months (HR: 2.18 (1.57-3.03), but not in children aged 0-9 years. [39] …”
Section: Resultsmentioning
confidence: 99%
“… [34] Finally, in another US study, new-onset diabetes was increased in children aged 10-18 years at 3 months (HR: 2.40 (1.62-3.56)) and 6 months (HR: 2.18 (1.57-3.03), but not in children aged 0-9 years. [39] …”
Section: Resultsmentioning
confidence: 99%
“…A total of 853 studies were screened. The exclusion process yielded 8 studies 3 , 5 , 9 , 19 23 conducted in 3 countries. Barret et al was reported in this meta-analysis as two independent studies 3 .…”
Section: Resultsmentioning
confidence: 99%
“…The MetroHealth System, Cleveland OH, IRB determined research using TriNetX is not Human Subject Research and therefore IRB exempt. We previously used TriNetX Analytics network platform to study risk factors and outcomes of COVID-19 and other diseases [6][7][8][9][10][11][12][13][14][15][16] , including examining the incidence rates and clinical outcomes of COVID-19 with the Omicron and Delta variants in children ≤ 5 years of age 6 .…”
Section: Study Populationmentioning
confidence: 99%